Public and Political Communication: An Amphibology to think the Common - Arancibia Carrizo, Juan Pablo (Re-presentaciones: Periodismo, comunicación y sociedad, 2023)
The present article examines from a genealogical perspective the amphibology that exists between «Public Communication» and «Political Communication». In contemporary communication literature, there is a persistent ambiguity and a difficulty in accurately identifying the distinction between the two notions. This confusion and impossibility originates, from our perspective, in the omission of two classic Greek categories that allowed to differentiate, but also to articulate these two dimensions or times of the public sphere: «politeia» and «politeuma».
Keywords: Public Communication; Political Communication; Politeia; Politeuma; Common